DEVELOPMENT OF METHODS FOR THE QUANTITATIVE DETERMINATION OF 1-FOILHAT-1,3,5-TRIIN IN THE ESSENTIAL OIL OF GRASS SUCCESSION DROOPING - Yana Fedorovna Korobova; Tatyana Dmitrievna Mezenova; Aida Mahmudovna Nasukhova; Dmitriy Alexeyevich Konovalov (Современная наука и инновации)
A method for the quantitative determination of 1-phenylhepta-1,3,5-triin in the essential oil of grass of Bidens cernua, allows you to control the main active compound - polyacetylene compound of above-ground parts of the plant. Methods validated and meet the necessary requirements in terms of linearity, accuracy and convergence. This procedure is recommended for the study of the chemical composition and the development of quality standards for the medicinal raw materials - grass of Bidens cernua.